ROKOK ELEKTRONIK DAN SILANG SENGKARUT KOMUNIKASI - Istiqomatul Hayati; Reza Helmi; Eka Wenats Wuryanta (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2020)
E-cigarette consumption increases as smoke-free campaigns worldwide. Some consider the consumption of e-cigarettes is a healthy way to quit smoking. E-cigarettes are considered to help eliminate smoking habit. In fact, quitting smoking cannot be replaced with e-cigarette. Because, in vape there are glycerin, nicotine, and seasoning placed in the cartridge. Honestdoc writes the glycerin or propylene propylene to produce moisture. In effect, an electronic smoker will be irritated to a person's filtration channel. The purpose of this research is to see how Tempo.co and Kompas write news about the difference of communication in the Ministry of Trade and the Ministry of Health who have not published rules regarding the restriction or prohibition of electronic cigarette. Critical discourse analysis used to dissect government communication about electronic cigarette consumption, which isnt in line, such as written Kompas.com and Tempo.co from the start of this issue revolving until now. Both media shows, the government's plainness to publish rules regarding the restriction or prohibition e-cigarettes due to confusion to health of people or save investments. Consequently, until now, there isnt clear regulation about this. Regulations are limited to the new imposition of excise imposed on July 1st 2018.